Counseling on the Benefits of White Turmeric (Curcuma mangga Val.) and Probiotic Foods in the Writing Farmer Group - Dwiyati Pujimulyani; Wisnu Adi Yulianto (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Recently in Indonesia, there has been an increase in degenerative diseases such as heart disease caused by high blood fat levels, namely triglycerides and cholesterol. Prevention of heart disease can be done by adjusting the diet and consuming healthy foods that contain hypocholesterolemic properties and probiotics. Compounds that are thought to have hypocholesterolemic properties are curcuminoids in rhizomes such as white saffron (Curcuma mangga Val.). In addition, probiotic food is very good for the body because it contains microorganisms that can support the digestive and immune systems. Sumbersari village is in Moyudan sub-district, Sleman district, Special Region of Yogyakarta. Most of the people work in agriculture as owners or cultivators. The survey results of the service team showed that the community did not know how to cultivate, the benefits of white saffron, how to process instant powder and the benefits of probiotic foods that can reduce the risk of degenerative diseases such as heart disease. Counseling was held on Saturday 29 July 2023 which was attended by 36 people. The first step of the service activity is the coordination of cooperation with partners to motivate the community of the Farmer Group in Menulis hamlet to be willing to participate wholeheartedly in all activities. At the implementation stage, counseling was carried out to broaden the insight of the Farmers Group of Menulis hamlet related to the cultivation and benefits of white saffron and probiotic food. In addition to counseling activities, there was also a distribution of white saffron seeds, white saffron capsules, instant powder